Pengaruh Modal Manusia, Modal Fisik, Dan Tingkat Partisipasi Angkatan Kerja Terhadap Pertumbuhan Ekonomi Di Provinsi Lampung - Citra Putri Natalia; Heru Wahyudi (Departement of Mathematics Education, 2024)
The purpose of this research is to analyze the effect of human capital, physical capital, and labor force participation rate on economic growth in Lampung Province during the research period of 2017–2022. This research used panel data analysis with the Fixed Effect Model (FEM). Economic growth is used as the dependent variable, while human capital, physical capital, and labor force participation rate are used as independent variables. Based on the results, human capital and physical capital have a positive and significant effect on economic growth in Lampung Province. Meanwhile, the Labor Force Participation Rate (LFPR) shows a positive but insignificant effect on economic growth in Lampung Province. These results indicate that an increase in human capital and physical capital leads to an increase in economic growth. However, the labor force participation rate has not been able to influence the increase in economic growth in Lampung Province.